Assessing the climate change vulnerability of reptile and amphibian species found in Table Mountain National Park - Harper, Jack (University of Cape Town, 2020)
It is increasingly apparent that climate change and its associated impacts are a major threat to the rich biodiversity of the Cape floristic region. As the knowledge of the associations between biological traits and climate change impacts strengthens it has become clear that the assessment of climate change vulnerability is a key consideration in the management of biodiversity. This study is the first attempt to use a trait-based approach at the scale of a single national park, focusing on the climate change vulnerability of reptile and amphibian species found in Table Mountain National Park (including historically present species). The park and its immediate surrounding areas are home to a rich diversity of herpetofauna including the Critically Endangered Table Mountain ghost frog (Heleophryne rosei), Rose's mountain toadlet (Capensibufo rosei) and micro frog (Microbatrachella capensis), and the Endangered western leopard toad (Sclerophrys pantherina). Amphibian and reptile-specific assessment frameworks of biological and ecological traits were designed to identify the species most sensitive and least able to adapt to climate change pressures. Using a combination of a literature review and expert consultation, 18 species of amphibian and 41 species of reptile were assessed. The assessment highlighted that, in the worst-case scenario, 85% of the park's reptile species and 67% of the park's amphibian species are predicted to be highly vulnerable to climate change. The southern adder (Bitis armata), Cape long-tailed seps (Tetradactylus tetradactylus), Table Mountain ghost frog (Heleophryne rosei) and the Lightfoot's moss frog (Arthroleptella lightfooti) were identified as being the species most vulnerable to climate change within their respective taxa. All three of the Critically Endangered amphibian species were identified as having both high sensitivity and low adaptive capacity to climate change. Among the focal reptile species, climate change vulnerability was independent of current IUCN Red List status, highlighting that species currently not identified to be under threat by other anthropogenic pressures could imminently become threatened by climate change. Spatiallyexplicit presentation of the assessment output will help prioritise the management of areas within Table Mountain National Park that contain a high diversity of climate-vulnerable species. By reducing the threats from other human-associated impacts to these species, and by identifying when direct intervention is appropriate, the park's management can give these species the best opportunity of persistence in an uncertain climate future.